Desenvolvimento de plantas anãs para a obtenção de híbridos de tomate do tipo salada - Finzi, Rafael Resende (2020)
Combine broad-spectrum pest resistance, higher yield and fruit nutritional quality on a single hybrid is a challenge for round tomato breeders. The use of a dwarf line to obtain mini-tomato hybrids has provided advantages and can be an excellent alternative to achieve these objectives in the round tomatoes. However, the exploitation of the benefits provided by the use of the dwarf parent in tomato round hybrids is not yet a reality. The development of dwarf lineages of this segment is the first step to be performed and backcrossing is an appropriate method to develop such lineages. In addition to backcrossing, it is also important to assess the progress of dwarf populations obtained after advancing in the self-fertilization cycle. Therefore, the objective of this work was to select BC1F2 and BC1F3 populations of dwarf tomato type round with agronomic potential, fruit quality and resistance to pests. This research was carry out in two stages: first, the performance of dwarf populations obtained after a backcross (BC1F2) and, then, the performance of dwarf populations obtained after a selffertilization (BC1F3) of plants from populations selected in BC1F2. Both trials were carried out at the vegetable trial station at the Federal University of Uberlandia – Monte Carmelo Campus, MG, Brazil. For the first experiment, was used a randomized block design with 15 treatments and 3 replications. The genetic material evaluated consisted of 12 dwarf tomato BC1F2 populations, plus both parents (recurrent and donor) and a commercial hybrid. It was observed that average fruit weight in the dwarf populations increased significantly after the first backcross, with some fruits exhibiting a similar shape to round tomatoes. Selection of the populations UFU-DTOM3, UFU-DTOM5, UFU-DTOM7, UFU-DTOM9 and UFU-DTOM10 resulted in an estimated 6% increase in the number of locules, transverse diameter, TD/LD ratio and average fruit weight. The dwarf populations UFU-DTOM7 and UFU-DTOM10 were the most promising for develop inbred lines with round fruits. For the second study, the genetic material evaluated consisted of ten BC1F3 dwarf populations, originated from self-fertilization of plants selected in dwarf populations BC1F2 plus both parents (recurrent and donor) and a commercial hybrid. In general, there was an increase of up to 1035% in the average fruit mass of the dwarf populations in relation to the donor parent. In addition, some dwarf populations showed fruits with 49% more lycopene in relation to the commercial hybrid, as well as higher levels of acylsugars in the leaves (273%). The dwarf populationUFU-DW22 stood out, presenting agronomic potential, higher levels of lycopene in fruits and high levels of acylsugars, which gives resistance to pests. In order to future work with the BC1F3 dwarf plants in this study, is suggest to perform the second backcross to obtain lines and, subsequently, compact hybrids from dwarf lines of the round type.